Queering STEM culture in US higher education : navigating experiences of exclusion in the Academy - Cross, Kelly J.; Farrell, Stephanie; Hughes, Bryce (New York ; London : Routledge, Taylor & Francis Group, 2022)
Adopting an intersectional lens, this timely volume explores the lived experiences of members of the queer and trans community in post-secondary STEM culture in the US to provide critical insights into progressing socially just STEM education pathways. Offering contributions from students, faculty, practitioners, and administrators, the volume highlights prevailing issues of heteronormativity and marginalization across a range of STEM disciplines. Autoethnographic accounts place minority experiences within the broader context of social and cultural phenomena to reveal subtle and overt forms of exclusion, and systematic barriers to participation in STEM professions, academia, and research. Finally, the book offers key recommendations to inform future research and practice. This volume will benefit researchers, academics, and educators with an interest in higher education, engineering education, and the sociology of education more broadly. Those involved with diversity, equity, and inclusion within education, queer theory, and gender and sexuality studies will also benefit from this volume.--
Part I. Queer students : Where do I fit in STEM? -- Part II. Queer staff : How can I create safe spaces for queer people in STEM? -- Part III. Queer faculty : How can I build community for the queer in STEM? -- Part IV. Queer allies, allyship, and advocates : How can I support the queer in STEM?
Keywords: Sexual minorities in higher education -- United States; Sex differences in education -- United States; Science -- Study and teaching (Higher) -- Social aspects -- United States; Technology -- Study and teaching (Higher) -- Social aspects -- United States; Engineering -- Study and teaching (Higher) -- Social aspects -- United States; Mathematics -- Study and teaching (Higher) -- Social aspects -- United States; EDUCATION / Higher; EDUCATION / Multicultural Education